Progress in Research on Sustainable Urban Renewal Since 2000: Library and Visual Analyses - Bohong Zheng (Sustainability, 2021)
Urban renewal is an ideal approach to promoting the value of the urban fabric and improving the sustainability of the urban environment. This study, which shows the continuity of research on sustainable urban renewal, aimed to identify sustainable urban renewal literature based on a library analysis of scientific research since 2000. A total of 3971 scientific papers from the SCIE (Science Citation Index Expanded) and SSCI (Social Sciences Citation Index) databases were reviewed to examine how research concerning “sustainable urban renewal” has emerged and developed in the past 20 years. The h-indices and impact factors of the most relevant journals in urban renewal and sustainable development since 2000 were analyzed. The most frequently cited articles were analyzed using analysis of social networks (VOSviewer). The results revealed potential future focuses of research and guidelines that link urban renewal and sustainability: the engagement of all stakeholders in the decision-making process; the involvement of residents in projects; the development of cooperation between towns and cities; the preservation and reuse of built and industrial heritage while respecting environmental law; and, finally, the search for new financing techniques. These potential future research topics were analyzed in four research areas so that sustainable development can easily be integrated into an urban renewal project.